Immunophenotypic and genotypic features, clinical characteristics, and treatment outcome of adult pro-B acute lymphoblastic leukemia: results of the German Multicenter Trials GMALL 03/87 and 04/89 - Ludwig, Wolf-Dieter; Rieder, Harald; Bartram, Claus R.; Heinze, Barbara; Schwartz, Stefan; Gassmann, Winfried; Löffler, Helmut; Hossfeld, Dieter K.; Heil, Gerhard; Handt, Susanne; Heyll, Axel; Diedrich, Helmut; et al. (Blood, 1998)
In contrast to childhood acute lymphoblastic leukemia (ALL), the cell-biological features, clinical characteristics, and treatment outcome of CD10− pro-B ALL have not yet been determined in larger series of adult patients. Therefore, we studied 57 adult patients with newly diagnosed pro-B ALL (median age, 30 years) enrolled in two consecutive German multicenter ALL studies (03/87 and 04/89). Extensive immunophenotypic characterization of leukemic blasts could be performed on all patients, whereas adequate cytogenetic data were available in 33 cases and molecular studies in 18 cases, using reverse transcription-polymerase chain reaction to detect MLL-AF-4 transcripts. Twenty-two patients demonstrated a t(4;11)(q21;q23) and/or MLL-AF-4 rearrangements, and 6 patients had other structural abnormalities, including a t(9;22)(q34;q11) (N = 2). Nine patients had a normal karyotype. Patients with 11q23 abnormalities tended to be younger (median age, 29 years) and were characterized by male predominance (64%), hyperleukocytosis (median leukocyte count, 168 × 109/L), and a frequent coexpression of CD65s (64%) as compared with patients with other cytogenetic abnormalities or a normal karyotype. Twelve of 16 (75%) pro-B ALL patients in study 03/87 and 30 of 41 (73%) in study 04/89 achieved a complete remission (CR). Sixteen of 30 patients in study 04/89 remain in continuous CR (CCR) in contrast to only 2 of 12 patients in study 03/87. Interestingly, all 7 patients treated with high-dose cytarabine and mitoxantrone as consolidation in study 04/89 remain alive and leukemia-free. One patient in study 03/87 and 8 in study 04/89 underwent autologous (N = 2) or allogeneic (N = 7) bone marrow transplantation (BMT). The median remission duration was 420 days for patients in study 03/87 and has not yet been reached in study 04/89. The median survival time of all pro-B ALL patients was 571 days in study 03/87 and 747 days in study 04/89. Among the 22 patients with a t(4;11) and/or MLL-AF-4 rearrangements, 17 achieved a CR and 8 are still in CCR, of whom 4 underwent an allogeneic BMT. Remission duration and overall survival did not differ significantly between pro-B ALL patients with 11q23 abnormalities and those with a normal karyotype or other structural abnormalities. These data indicate that intensification of postremission treatment may improve the prognosis of adult pro-B ALL, including patients with a t(4;11). © 1998 by The American Society of Hematology.
Elektronische Reproduktion der Druck-Ausgabe 14. Dezember 2020
Gesehen am 08.01.2024